Tanggap Pertumbuhan dan Produksi Bawang Merah (Allium ascalonicum L.) Terhadap Dosis Pupuk Fosfat dan Asam Humat - Osmin Sipayung; Mariati Mariati; Meiriani Meiriani (Universitas Sumatera Utara, 2015)
The aims of the research was to analize the growth and yield response of shallots (Allium ascalonicum L.) on the doses of phospate fertilizer and humic acid. The research was conducted at Jl. Pasar 1 Ringroad Medan from August to November 2014, using a factorial randomized block design with two factors replicated three times. The first factor is the doses of phosphate fertilizers (90, 72, 54, 36 kg / ha) and the second is the doses of humic acid (0, 1.5, 3 kg / ha). Parameters observed were number of leaves, number of tillers, wet weight per sample, dry weight per sample, the rate of net assimilation, the rate of relative growth, and the rate of plant growth. The result showed that only number of leaves 4 week after planting was significantly affected by the interaction between fosfate fertilizers and humic acid, which the most number of leaves was 19.67 produced by combination of 36 kg/ha phosphate fertilizer and 3 kg/ha humat acid and at 5,6 and 7 week after planting was significantly affected by humic acid. Meanwhile, all other parameters observed were not significantly affected by all treatments.Keywords: Fosfate fertilizer, humic acid, shallots